Clinical Comparison of Overlapping Deletions of 19p13.3. Issue 5 (22nd April 2013) - Risheg, Hiba; Pasion, Romela; Sacharow, Stephanie; Proud, Virginia; Immken, LaDonna; Schwartz, Stuart; Tepperberg, Jim H.; Papenhausen, Peter; Tan, Tiong Y.; Andrieux, Joris; Plessis, Ghislaine; Amor, David J.; et al.
Abstract We present three patients with overlapping interstitial deletions of 19p13.3 identified by high resolution SNP microarray analysis. All three had a similar phenotype characterized by intellectual disability or developmental delay, structural heart abnormalities, large head relative to height and weight or macrocephaly, and minor facial anomalies. Deletion sizes ranged from 792 Kb to 1.0 Mb and included a common region arr [hg19] 19p13.3 (3, 814, 392–4, 136, 989), containing eight genes: ZFR2, ATCAY, NMRK2, DAPK3, EEF2, PIAS4, ZBTB7A, MAP2K2, and two non‐coding RNA's MIR637 and SNORDU37. The patient phenotypes were compared with three previous single patient reports with similar interstitial 19p13.3 deletions and six additional patients from the DECIPHER and ISCA databases to determine if a common haploinsufficient phenotype for the region can be established. © 2013 Wiley Periodicals, Inc.